VD_FINDINFO Plainte / 2012 / 39 vom 21. September 2012 - VD Tribunal cantonal (2012)
POURSUITE EN PRESTATION DE SÛRETÉS, RÉQUISITION DE POURSUITE, COMMANDEMENT DE PAYER, NULLITÉ | 38 LP, 67 al. 1 ch. 3 LP, 69 al. 1 LP, 69 al. 2 ch. 1 LP, 69 al. 2 ch. 2 LP